Copper oxide as a "self-cleaning" substrate for graphene growth. Issue 3 (29th January 2014) - Magnuson, Carl W.; Kong, Xianghua; Ji, Hengxing; Tan, Cheng; Li, Huifeng; Piner, Richard; Ventrice, Carl A.; Ruoff, Rodney S.
Abstract: Abstract : Commonly used techniques for cleaning copper substrates before graphene growth via chemical vapor deposition (CVD), such as rinsing with acetone, nitric, and acetic acid, and high temperature hydrogen annealing still leave residual adventitious carbon on the copper surface. This residual carbon promotes graphene nucleation and leads to higher nucleation density. We find that copper with an oxidized surface can act as a self-cleaning substrate for graphene growth by CVD. Under vacuum conditions, copper oxide thermally decomposes, releasing oxygen from the substrate surface. The released oxygen reacts with the carbon residues on the copper surface and forms volatile carbon monoxide and carbon dioxide, leaving a clean copper surface free of carbon for large-area graphene growth. Using oxidized electropolished copper foil leads to a reduction in graphene nucleation density by over a factor of 1000 when compared to using chemically cleaned oxygen free copper foil.